1997
DOI: 10.1007/s003300050187
|View full text |Cite
|
Sign up to set email alerts
|

Cervical diastematomyelia and syringohydromyelia in a myelomeningocele patient

Abstract: A case of cervical diastematomyelia and syringohydromyelia in a 16-year-old female myelomeningocele patient is reported. Progressive weakness of the upper extremity led to an MR examination of the brain and spine, which revealed hydrocephalus, Chiari II malformation, cervical diastematomyelia with a syringohydromyelic cavity in each hemicord and a large dural sac in the lumbar region. Operative therapy consisted of detethering and shunting of the two syringes. Soon after surgery her symptoms improved. The need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The term syringohydromyelia may be used to describe all fluid‐filled cavities in the spinal cord. It has been assumed that altered cerebrospinal fluid dynamics with a pressure gradient from the head to the spine play a significant role in the production of the syringohydromyelia although, as in our patient, many occurrences are asymptomatic (14).…”
Section: Discussionmentioning
confidence: 63%
“…The term syringohydromyelia may be used to describe all fluid‐filled cavities in the spinal cord. It has been assumed that altered cerebrospinal fluid dynamics with a pressure gradient from the head to the spine play a significant role in the production of the syringohydromyelia although, as in our patient, many occurrences are asymptomatic (14).…”
Section: Discussionmentioning
confidence: 63%
“…The combination of different dysraphic anomalies in a patient such as MMC and split cord, MMC and tethered cord, as well as split cord and tethered cord are well-known entities. Coexistence of lipoma, syringomyelia or dermal sinus tract with these pathologies is also documented in some series [3,4,5,6,7,8,9,10,11]. Although a high frequency of coexisting anomalies is well recognized, the association of seven distinct pathologies comprising hydrocephalus, Chiari malformation, split cord malformation, dermal sinus tract, MMC, and tethered cord is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…An association of MMC and split cord malformation is documented in 26–39% of the cases [3,4,5,6,7, 9, 10]. Type I split cord malformation is more frequently associated with MMC (75%) than type II split cord malformation [4, 6, 8, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Myeloschisis has been associated with various congenital malformations, such as lipoma, syringomyelia and Chiari malformations [8], and it is frequently associated with diastematomyelia, but only a few reports of myeloschisis with diastematomyelia are available [2, 3, 9]. Recent studies revealed that MRI and 3D CT are useful for the diagnosis of diastematomyelia [10, 11, 12], and in this case, the visible myeloschisis and underlying complex split cord formation as well as the septum were clearly revealed preoperatively using 3D CT and MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The pathology associated with this syndrome includes vertebral body malformation [1], syringomyelia [2], myeloschisis [3], lipomyelomeningocele [4], epidermoid cyst [5]and teratoma [6]. We report here a rare case of myeloschisis on the right hemicord of a diastematomyelia, which was successfully treated by removing the septum of the split cord and closure of the myeloschisis.…”
Section: Introductionmentioning
confidence: 96%